A comprehensive system of pharmaceutical care for drug misusers - Roberts Kay; Hunter Carole (BMC, 2004)
Abstract This article outlines the evolution of a community pharmacy-based supervised consumption of methadone program in Grater Glasgow. The formalization of this program in 1994 promoted full patient compliance with the methadone regimen and reduced seepage of the drug to the illicit market. 184 of the area's 215 community pharmacies now dispense methadone for the treatment of opiate dependence. Of these, 173 have a supplementary contract with the local health board to supervise the consumption of methadone on their premises. In addition 15 of "methadone" pharmacists are involved in the provision of a pharmacy based needle exchange scheme. This has been shown to be the most efficient and cost effective method of delivering clean injecting equipment to injecting drug users in the Greater Glasgow area. Glasgow's pharmacists' have now been involved in the methadone and needle exchange programs for more than ten years. The support needed by pharmacists and the steps that have been put in place to provide this level of commitment are described. The development of the Glasgow pharmacy based services to drug users has had a major impact on practice elsewhere in the United Kingdom.